Sleep Quality Improvements After MDMA‐Assisted Psychotherapy for the Treatment of Posttraumatic Stress Disorder. Issue 4 (10th June 2021) - Ponte, Linnae; Jerome, Lisa; Hamilton, Scott; Mithoefer, Michael C.; Yazar‐Klosinski, Berra B.; Vermetten, Eric; Feduccia, Allison A.
Abstract: Sleep disturbances (SDs) are among the most distressing and commonly reported symptoms in posttraumatic stress disorder (PTSD). Despite increased attention on sleep in clinical PTSD research, SDs remain difficult to treat. In Phase 2 trials, 3, 4‐methylenedioxymethamphetamine (MDMA)–assisted psychotherapy has been shown to greatly improve PTSD symptoms. We hypothesized that MDMA‐assisted psychotherapy would improve self‐reported sleep quality (SQ) in individuals with PTSD and be associated with declining PTSD symptoms. Participants in four studies ( n = 63) were randomized to receive 2–3 sessions of active MDMA (75–125 mg; n = 47) or placebo/control MDMA (0–40 mg, n = 16) during all‐day psychotherapy sessions. The PSQI was used to assess change in SQ from baseline to the primary endpoint, 1–2 months after the blinded sessions. Additionally, PSQI scores were measured at treatment exit (TE) and 12‐month follow‐up. Symptoms of PTSD were measured using the CAPS‐IV. At the primary endpoint, CAPS‐IV total severity scores dropped more after active MDMA than after placebo/control (−34.0 vs. −12.4), p = .003. Participants in the active dose group showed more improvement in SQ compared to those in the control group (PSQI total score Δ M = −3.5 vs. 0.6), p = .003. Compared to baseline, SQ had improved at TE, p < .001, with further significant gains reported at 12‐month follow‐up (TE to 12‐months Δ M = −1.0), p = .030. Data from these randomized controlled double‐blind studies provide evidence for the beneficial effects of MDMA‐assisted psychotherapy in treating SDs in individuals with PTSD. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Traditional Chinese MDMA 輔助心理療法治療創傷後壓力症後睡眠質量的改善 摘要 睡眠壓力症(SDs)是創傷後壓力症中最令人痛苦和最常見的症狀之一。儘管在臨床創傷後壓力症研究中對睡眠的關注度越來越高, 但SD仍然難以治療。在第二階段試驗中, 3, 4‐亞甲二氧基甲基苯丙胺(MDMA)輔助的心理治療已被證明可大大改善創傷後壓力症症狀。我們假設, MDMA輔助的心理治療會改善創傷後壓力症臨床治療者自我報告的睡眠質量(SQ), 並與創傷後壓力症症狀的下降有關。四項研究的參與者(n = 63)在全天心理治療過程中隨機接受了2‐3個療程的活性MDMA(75‐125 mg;n = 47)或安慰劑/控制MDMA(0‐40 mg;n, n = 16)。PSQI被用來評估從基線到主要終點的SQ變化, 即在盲法治療後1‐2個月。此外, PSQI分數在治療結束(TE)和12個月的隨訪中被測量。創傷後壓力症的症狀是用CAPS‐IV測量的。在主要終點, 活性MDMA後CAPS‐IV的總嚴重程度得分比安慰劑/對照組下降更多(‐34.0 vs. ‐12.4), p = .003。與對照組相比, 活性劑量組的參與者在SQ方面有更多的改善(PSQI總分ΔM = ‐3.5 vs. 0.6)。 p = .003. 與基線相比, SQ在TE時有所改善, P<0.001, 在12個月的隨訪中報告了進一步的顯著改善(TE到12個月的ΔM=‐1.0), P=0.030。這些隨機對照的雙盲研究的數據為MDMA輔助心理療法治療創傷後壓力症臨床治療者的SDs的有益效果提供了證據。 Simplified Chinese MDMA 辅助心理疗法治疗创伤后压力症后睡眠质量的改善 摘要 睡眠压力症(SDs)是创伤后压力症中最令人痛苦和最常见的症状之一。尽管在临床创伤后压力症研究中对睡眠的关注度越来越高, 但SD仍然难以治疗。在第二阶段试验中, 3, 4‐亚甲二氧基甲基苯丙胺(MDMA)辅助的心理治疗已被证明可大大改善创伤后压力症症状。我们假设, MDMA辅助的心理治疗会改善创伤后压力症临床治疗者自我报告的睡眠质量(SQ), 并与创伤后压力症症状的下降有关。四项研究的参与者(n = 63)在全天心理治疗过程中随机接受了2‐3个疗程的活性MDMA(75‐125 mg;n = 47)或安慰剂/控制MDMA(0‐40 mg;n, n = 16)。PSQI被用来评估从基线到主要终点的SQ变化, 即在盲法治疗后1‐2个月。此外, PSQI分数在治疗结束(TE)和12个月的随访中被测量。创伤后压力症的症状是用CAPS‐IV测量的。在主要终点, 活性MDMA后CAPS‐IV的总严重程度得分比安慰剂/对照组下降更多(‐34.0 vs. ‐12.4), p = .003。与对照组相比, 活性剂量组的参与者在SQ方面有更多的改善(PSQI总分ΔM = ‐3.5 vs. 0.6)。 p = .003. 與基線相比, SQ在TE時有所改善, P<0.001, 在12個月的隨訪中報告了進一步的顯著改善(TE到12個月的ΔM=‐1.0), P=0.030。這些隨機對照的雙盲研究的數據為MDMA輔助心理療法治療創傷後壓力症臨床治療者的SDs的有益效果提供了證據。